The Implementation of PSAK (Financial Accounting Standard) 109 to Increase Transparency and Accountability Zakat Governance in BAZNAS Jeneponto Regency - Mayasofa, Ira; Razak, Linda Arisanty; Sahib, Muhammad Khaedar (Al-Mal: Jurnal Akuntansi dan Keuangan Islam, 2024)
This research seeks to determine the accounting recording of zakat, infaq, and sadaqah at BAZNAS Jeneponto Regency in line with PSAK (Financial Accounting Standard) 109 when preparing financial statements, as well as to investigate the impact of PSAK 109 implementation to increase transparency and accountability at BAZNAS Jeneponto Regency. This research focuses on the National Amil Zakat Agency (BAZNAS) in Jeneponto Regency. This research employs descriptive qualitative methods. The data was gathered through interviews, observations, and documentation of BAZNAS Jeneponto Regency's financial statements for one semester (January 1 to  June 30, 2023). Based on the findings of this research, BAZNAS in Jeneponto Regency prepares its financial statements in line with the guidelines of the PSAK 109, as evidenced by the financial statements presented separately.Regarding transparency and accountability, BAZNAS Jeneponto Regency has prepared its financial statements in compliance with the guidelines of PSAK 109. However, BAZNAS Jeneponto Regency cannot be considered entirely transparent and accountable because of several factors, like the financial statement that has not been presented, namely the report on changes in managed assets. The financial reports cannot be accessed because they have not been audited for this period. Furthermore, the BAZNAS website was only created two months ago.